Phytotechnical performance and selection of 15 introduced lines of Lathyrus sativus L. in Jauja, Junín - Camarena, Felix (2022)
Fifteen lines of Lathyrus sativus L. introduced from ICARDA Syria, and a local control in the 2018 and 2019 agricultural campaigns at the El Mantaro Experimental Station, of the National University of Central Peru in Jauja, Junín, located at an altitude of 3,300 meters above sea level with the objective of evaluating the yield of dry grain and its morphological and physiological components of the lines under spring-summer sowing in dry conditions. The lines that stood out in grain yield greater than 700 kg/ha, with pods 4 cm long, more than 100 pods per plant, greater than two grains per pod and weight of 100 seeds greater than 20 g, were the local control. T16, followed by lines L3556 and L3030. While the L3556 line was precocious with 63 days to flowering and 180 days to physiological maturity. The improved lines of Lathyrus in the environment of average temperature of 13.04 °C, a relative humidity of 57.2 % and a rainfall of 667.2 mm had a good performance, earliness and can be evaluated in marginal lands of the Andean zone for being a genetic reservoir. that will increase the genetic variability of the ground pea that is grown as an underutilized crop in the Sierra de Ancash to buffer against climate change.